SPECIFIC FEATURES OF THE QUALIFICATION OF CRIMES AGAINST THE FREEDOM OF A PERSON - Sodikovich, Toshev Otabek (Antis Publisher, 2024)
In this article, the author examines the specifics of qualifying crimes against human freedom. In particular, the signs of the objective side of crimes of this category are comprehensively studied, the results of scientific research, views and approaches of scientists and researchers regarding the qualification of crimes against human freedom and their differentiation from crimes with a similar composition are analyzed. Based on the results of the study, the author provided the corresponding scientific and theoretical conclusions.